Constraints on the NMSSM from the Oblique Parameters - Markos Maniatis; York Schröder (Advances in High Energy Physics)
Electroweak precision measurements, encoded in the oblique parameters, give strong constraints on physics beyond the Standard Model. The oblique parameters